The effects of feed moisture and dried coconut meal content on the physicochemical, functional, and sensory properties of gluten-free Riceberry rice flour-based extruded snacks - Piayura, Sumeth; Itthivadhanapong, Pimchada (Frontiers in Sustainable Food Systems, 2023)
The objective of this study was to develop an expanded snack from Riceberry rice flour (RBF) and dried coconut meal (DCM), a by-product of coconut milk production, using a twin-screw extruder. A 3 x 3 factorial design was employed to investigate the effects of feed moisture contents (18, 21, and 24%) and DCM levels (0, 5, and 10%) on the physicochemical, functional, and sensory properties of the products. The results showed that increasing feed moisture content significantly reduced the cold peak viscosity but had no significant effect on the hot peak viscosity. DCM was the dominant factor affecting the hot peak viscosity. The substitution of DCM led to a decrease in the expansion of the extrudates while increasing the L* and b* values. The texture parameters were affected by both feed moisture and DCM, where increased feed moisture resulted in more rigid structures with higher density and hardness but lower crispiness. Antioxidant levels in the final product decreased by approximately 64 to 70% and 10 to 25%, as determined by DPPH and FRAP assays, respectively, compared to the initial RBF. However, the antioxidant levels remained high in the final product. Feed moisture content had no effect on the antioxidant activity as measured by the DPPH and FRAP assays. The total phenolic content (TPC) of the extrudates decreased as feed moisture and DCM content increased. Furthermore, the anthocyanin content (ATC) decreased when RBF was substituted with DCM. The sensory evaluation revealed that the product with 18% feed moisture content and 10% DCM had the highest overall liking score. These findings offer valuable insights into the potential use of a twin-screw extruder for developing expanded snacks from RBF and DCM and could be useful for further research in this area.